Genetics, Diagnosis, and Management of Hürthle Cell Thyroid Neoplasms - McFadden, David G.; Sadow, Peter M. (Frontiers in Endocrinology, 2021)
Hürthle cell lesions have been a diagnostic conundrum in pathology since they were first recognized over a century ago. Controversy as to the name of the cell, the origin of the cell, and even which cells in particular may be designated as such still challenge pathologists and confound those treating patients with a diagnosis of “Hürthle cell” anything within the diagnosis, especially if that anything is a sizable mass lesion. The diagnosis of Hürthle cell adenoma (HCA) or Hürthle cell carcinoma (HCC) has typically relied on a judgement call by pathologists as to the presence or absence of capsular and/or vascular invasion of the adjacent thyroid parenchyma, easy to note in widely invasive disease and a somewhat subjective diagnosis for minimally invasive or borderline invasive disease. Diagnostic specificity, which has incorporated a sharp increase in molecular genetic studies of thyroid tumor subtypes and the integration of molecular testing into preoperative management protocols, continues to be challenged by Hürthle cell neoplasia. Here, we provide the improving yet still murky state of what is known about Hürthle cell tumor genetics, clinical management, and based upon what we are learning about the genetics of other thyroid tumors, how to manage expectations, by pathologists, clinicians, and patients, for more actionable, precise classifications of Hürthle cell tumors of the thyroid.